Activities that related to feeding behaviour of sugar glider (Petaurus breviceps) in captivity at night - WARTIKA ROSA FARIDA; ARIA PERDANA; DIDID DIAPARI; ANITA SARDIANA TJAKRADIDJAJA (Society for Indonesian Biodiversity, 2005)
Activities that related to feeding behaviour of sugar glider (Petaurus breviceps) in captivity at night study on activity that related to feeding behaviour of sugar glider in captivity of small mammals at night has been conducted at the Division of Zoology, Research Center for Biology-LIPI, Bogor. Feeds consisted of passion fruit, banana, guava, papaya, sweet corn, coconut, and bread and were given ad libitum. Four sugar glider consisting of two males and females were place in two cages. One zero sampling method was used to observe daily activity with interval every 15 minutes which was divided in two periods (06.00-11.45 pm and 00.15-06.00 am). Result of behaviour observation showed that feeding activity (13.65%), drinking activity (0.58%), urination activity (4.71%) and defecation activity (5.93%). Other activities are locomotion, grooming, and resting activities 42.59%; 23.54%; and 9.01%. Male and female sugar gliders different in their feeding activities and locomotion.Key words: feeding behaviour, sugar glider, captivity, night.